ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA POKOK BAHASAN SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMK PP GMIM TOMOHON - Regar, Vivian; Kumesan, Selfie; Sawotong, Olivie (Universitas Negeri Manado, 2020)
ABSTRACT. This research was conducted to describe the errors made by students in solving the mathematics essays problem on two-variable linear equations system based on the Newman procedure. Â This research is a descriptive study with a qualitative approach. Subjects in the study are class X in SMK PP GMIM Tomohon 2019/2020 academiks year. The instrument used in this study were test and interview questions. Data Â collection techniques in this study were through the matter essays test mathematics system of two-variable linear equations and interviews. Data analysis techniques are carried out in three stages, namely data reduction, data presentation, and conclusion drawing. The analysis framework was developed based on the Newman error. The results of the study obtained 5 types of errors namely reading errors, understanding errors, transformation errors, process skill errors and writing error answers. Factors causing these errors, in general, is because of the intentions of the problem into a mathematical model, less capturing information from the teacher and less thorough in working on the problems. Keywords: Error analysis, Newman procedure, SPLDV